Reinsertion wages in the job market considering the Programa Seguro-Desemprego Unemployment Insurance Program in Brazil - Amorim, Domingos Isaias Maia (2021)
This work provides new estimates of the effect of the Brazilian Unemployment Insurance Program (Programa Seguro-Desemprego) at the national level and disaggregating the data considering urban and rural areas, using data from the National Household Sample Survey (Pesquisa Nacional de Amostra Por Domicílio - PNAD) on individuals for the year 2015. The methodology applied for empirical analysis is the Regression Discontinuity Design (RDD), using added covariates and entropy balancing. Our objective is to analyze if there is an effect of the unemployment benefit on reinsertion wages, and if it there is a positive relationship, based on the theoretical references of the Human Capital Theory and Job Search models. Among the main results found, the unemployment benefit program does not seem to exercise any significant change in the reinsertion wage, except for workers in the rural environment. It was also found that males receive lower reinsertion wages than females, and that the Northeast region of Brazil features the highest reinsertion wages.